The dynamic thermal properties of aerogel-incorporated concretes. (18th July 2022) - Strzałkowski, Jarosław; Garbalińska, Halina
Highlights: Very good heat wave damping properties of aerogel-incorporated concretes. Relatively high values of the volumetric specific heat for composites with aerogels. High internal thermal admittance of aerogel-incorporated concretes. Good low periodic thermal transmittance of aerogel-incorporated concretes. High relations between the thermal transmittance to concrete density and heat flux. Abstract: This study characterizes the dynamic thermal properties of aerogel-incorporated cement composites and other lightweight concretes. The tested specimens were prepared based on three types of aggregates: expanded clay, sintered fly ash aggregate and natural stone aggregate as a reference. The primary method of increasing the overall composite porosity was to prepare specimens by adding aerogel particles. A second method of increasing the cement matrix porosity was obtained using an air-entraining agent. The microstructure of the tested concretes was examined by mercury porosimetry. The novelty of the manuscript is that it presents the comparison of dynamic properties of concretes with the addition of aerogel and other types of lightweight concretes. Thermal properties tests were performed utilizing a non-stationary method. Based on experimentally obtained thermal properties, the values of dynamic thermal characteristics of the tested composites were calculated. The essential part of the experimental research were the tests carried out in non-stationary heat flow conditions in the analyzed composites. The aim of this research was to assess the influence of the thermal properties of a given composite on its behavior in changing temperature conditions. Having the data of the temperature change in specimens and the thermal properties of the tested composites, the total temperature increase, change of the accumulated thermal energy, heat flux, and densities were determined. Based on the experimental data, relationships between physical properties and dynamic thermal characteristics were evaluated.